Local structural transformations in the fcc lattice in various contact interaction. Molecular dynamics study; Physical Mesomechanics; Vol. 15, iss. 3 - Psakhie S. G. Sergey Grigorievich; Zolnikov K. P.; Dmitriev A. I. Andrey Ivanovich; Kryzhevich D. S.; · Nikonov A. Yu. (2012, 2012)
Title screen